1986
DOI: 10.1126/science.3787260
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Human Gene Closely Related to the abl Proto-Oncogene

Abstract: solar energy deposition into its atmosphere by a factor of 2.5 (17). The periodicity of albedo variations appears to provide an input to global planetary weather systems on a short time scale relative to Neptune's 164-year period of revolution around the sun. Neptune's orbit is almost perfectly circular, so its changing distance from the sun caused only an insignificant 0.5% decrease in total insolation since 1972. What appears remarkable is the extraordinary sensitivity of Neptune's atmosphere to the modulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
31
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(31 citation statements)
references
References 48 publications
0
31
0
Order By: Relevance
“…A 90 kDa C-terminal domain includes potential actin-and DNA-binding domains, a nuclear localization signal, and binding sites for the adapter proteins Crk/CRKL, Grb2 and Nck Ren et al, 1994). c-Abl and the Arg kinase (product of the abl related gene) share 90 ± 95% identity in the SH2, SH3 and catalytic domains, whereas their C-terminal parts are much more diverse, with only approximately 30% overall identity (Kruh et al, 1986(Kruh et al, , 1990.…”
Section: Introductionmentioning
confidence: 99%
“…A 90 kDa C-terminal domain includes potential actin-and DNA-binding domains, a nuclear localization signal, and binding sites for the adapter proteins Crk/CRKL, Grb2 and Nck Ren et al, 1994). c-Abl and the Arg kinase (product of the abl related gene) share 90 ± 95% identity in the SH2, SH3 and catalytic domains, whereas their C-terminal parts are much more diverse, with only approximately 30% overall identity (Kruh et al, 1986(Kruh et al, , 1990.…”
Section: Introductionmentioning
confidence: 99%
“…The N-terminal regions of c-Abl and Arg share ϳ90% identity and, as found in members of the Src family, contain tandem SH3, 1 SH2, and tyrosine kinase domains (1,2). Recent studies have shown that the cytoplasmic forms of c-Abl and Arg are activated in the cellular response to oxidative stress (3)(4)(5).…”
mentioning
confidence: 99%
“…The mammalian c-Abl and Arg nonreceptor tyrosine kinases are expressed widely in adult tissues (1)(2)(3). The N-terminal regions of c-Abl and Arg share ϳ90% identity and, as found in members of the Src family, contain tandem Src homology 3 (SH3), 1 SH2, and tyrosine kinase (SH1) domains.…”
mentioning
confidence: 99%